Divergent post-breeding spatial habitat use of Laysan and black-footed albatross - Jordan, Fredrick Dallas; Shaffer, Scott A.; Conners, Melinda G.; Stepanuk, Julia E. F.; Gilmour, Morgan E.; Clatterbuck, Corey A.; Hazen, Elliott L.; Palacios, Daniel M.; Tremblay, Yann; Antolos, Michelle; Foley, David G.; Bograd, Steven J.; et al. (Frontiers in Ecology and Evolution, 2022)
Understanding the at-sea movements of wide-ranging seabird species throughout their annual cycle is essential for their conservation and management. Habitat use and resource partitioning of Laysan (Phoebastria immutabilis) and black-footed (P. nigripes) albatross are well-described during the breeding period but are less understood during the post-breeding period, which represents ~40% of their annual cycle. Resource partitioning may be reduced during post-breeding, when birds are not constrained to return to the nest site regularly and can disperse to reduce competitive pressure. We assessed the degree of spatial segregation in the post-breeding distributions of Laysan (n=82) and black-footed albatrosses (n=61) using geolocator tags between 2008-2012 from two large breeding colonies in the Northwestern Hawaiian Islands, Midway Atoll and Tern Island. We characterized the species- and colony-specific foraging and focal distributions (represented by the 95th and 50th density contours, respectively) and quantified segregation in at-sea habitat use between species and colonies. Laysan and black-footed albatross showed consistent and significant at-sea segregation in focal areas across colonies, indicating that resource partitioning persists during post-breeding. Within breeding colonies, segregation of foraging areas between the two species was more evident for birds breeding at Tern Island. Spatial segregation decreased as the post-breeding season progressed, when spatial distributions of both species became more dispersed. In contrast to studies conducted on breeding Laysan and black-footed albatross, we found that sea surface temperature distinguished post-breeding habitats of black-footed albatrosses between colonies, with black-footed albatrosses from Midway Atoll occurring in cooler waters (3.6°C cooler on average). Our results reveal marked at-sea segregation between Laysan and black-footed albatross breeding at two colonies during a critical but understudied phase in their annual cycle. The observed variation in species-environment relationships underscores the importance of sampling multiple colonies and temporal periods to more thoroughly understand the spatial distributions of pelagic seabirds.